2019
DOI: 10.1093/sleep/zsz033
|View full text |Cite
|
Sign up to set email alerts
|

Circadian phenotype impacts the brain’s resting-state functional connectivity, attentional performance, and sleepiness

Abstract: Introduction Functional connectivity (FC) of the human brain’s intrinsically connected networks underpins cognitive functioning and disruptions of FC are associated with sleep and neurological disorders. However, there is limited research on the impact of circadian phenotype and time of day on FC. Study Objectives The aim of this study was to investigate resting-state FC of the default mode network (DMN) in Early and Late circadian phenotypes over a socially constrained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
82
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 64 publications
5
82
5
Order By: Relevance
“…The MCTQ-chronotype and its assessment of sleep phase have been validated against biochemical biomarkers, such as dim-light melatonin onset (DLMO) [18,[40][41][42] and cortisol [42], and objective behavioral measures of circadian phase (activity acrophase, and sleep behavior from logs or actimetry) [18,43,44]. They are all significantly correlated with MSFsc as one would expect if they are all valid biomarkers for phase of entrainment (the system state) and thus vary more of less together.…”
Section: Mctq-chronotyping: Pros and Consmentioning
confidence: 99%
“…The MCTQ-chronotype and its assessment of sleep phase have been validated against biochemical biomarkers, such as dim-light melatonin onset (DLMO) [18,[40][41][42] and cortisol [42], and objective behavioral measures of circadian phase (activity acrophase, and sleep behavior from logs or actimetry) [18,43,44]. They are all significantly correlated with MSFsc as one would expect if they are all valid biomarkers for phase of entrainment (the system state) and thus vary more of less together.…”
Section: Mctq-chronotyping: Pros and Consmentioning
confidence: 99%
“…Converging lines of evidence point to the precuneus as a key neural substrate for diurnal preference and chronotype. Recent resting-state FMRI studies have reported reduced precuneal functional connectivity in young adult late-type individuals as compared to morning-types [18,19] and structural MRI studies -again in younger adults -have demonstrated greater grey matter volume in the same region [28,29]. More generally, task-based FMRI studies indicate a role for the precuneus in a range of paradigms including social processing.…”
Section: Discussionmentioning
confidence: 99%
“…The functional and structural substrates of diurnal preference and chronotype are poorly understood, largely due to the paucity of studies exploring these questions. Functional Magnetic Resonance Imaging (FMRI) studies of circadian typology have reported effects of chronotype/diurnal preference on attention [10,11], language comprehension [12], inhibition [13], working memory [14], reward processing [15,16], emotional processing [17] and resting connectivity [18,19] -although see Fafrowicz [20] who reported no effect of diurnal preference on resting-state connectivity as measured by ALFF (Amplitude of Low Frequency Fluctuations -an index of total power within a predefined frequency range [20]). Interpretation of the above findings is limited due to the relatively small number of studies and, to date, lack of replication.…”
Section: Introductionmentioning
confidence: 99%
“…The MCTQ has been applied in many different countries: Japan ( Kitamura et al, 2014 ); Korea ( Suh et al, 2018 ); Brazil ( Miguel et al, 2014 ; Pilz et al, 2018b ); and several European countries: Poland ( Jankowski, 2015 ), Germany ( Roenneberg et al, 2003 ; Kuhnle, 2006 ), Italy ( Ghotbi et al, 2019 ), and Netherlands ( Zavada et al, 2005 ). The MCTQ has been compared with the MEQ ( Zavada et al, 2005 ; Kitamura et al, 2014 ; Miguel et al, 2014 ; Suh et al, 2018 ) and has been validated against DLMO ( Kitamura et al, 2014 ; Kantermann et al, 2015 ; Facer-Childs et al, 2019 ), cortisol ( Facer-Childs et al, 2019 ), and actimetry, for extreme chronotypes ( Facer-Childs et al, 2019 ), for young adults ( Santisteban et al, 2018 ), for communities with different levels of urbanization ( Pilz et al, 2018b ), and for shift workers ( Juda et al, 2013b ). Recently, an ultrashort version (μMCTQ) has been created and validated against DLMO and actimetry ( Ghotbi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%